Measuring Legislative Power: An Expert Reweighting of the Fish‐Kroenig Parliamentary Powers Index. Issue 2 (10th November 2016) - Chernykh, Svitlana; Doyle, David; Power, Timothy J.
Abstract : The Parliamentary Powers Index (PPI) developed by Fish and Kroenig (2009) is the most important effort to date to measure legislative power in cross‐national perspective, but it has been criticized on both theoretical and methodological grounds. We build on the 32‐item PPI to develop an alternative indicator of legislative strength that is based on an expert survey of 296 political scientists in 2014. We reweight each of the powers by expert opinion, creating a new Weighted Legislative Powers Score (WLPS) for the 158 national legislatures in the Fish and Kroenig data set. In addition, the article reports the expert‐assigned weight factors for the entire set of 32 powers contained in the original PPI, thus allowing researchers to innovate alternative, disaggregated indicators of legislative power.